Daya Tetas Telur Aedes aegypty Strain Japan Yang Disimpan Selama Seminggu Pada Suhu Ekstrem - Surya Permadi, I Gede Wempi; Taviv, Yulian; Ambarita, Lasbudi Pertama (Bioeksperimen: Jurnal Penelitian Biologi, 2019)
Dengue Hemorrhagic Fever (DHF) is one of the environmental health problems that several case increasing the number of patients and the wider area of distribution. The spread of dengue is influenced by several factors such as the vector disease, the behavior of people and the environment. In some sub-tropical countries is like  in the winter season , a number of   Aedes albopictus is found the eggs can still hatch at temperatures 0,5?C. Eggs that will be tested for each treatment amounted to 100 eggs and had been through the process selected.  The research carried in Parasitology and Entomology Labolatories, South Sumatra. The research was conducted from March to December 2014. In a multivariate test showed that the interaction of temperature and storage time affect the hatchability of eggs of Aedes aegypti strain Japan. Humidity and temperature can influence one of the insects are mosquitoes. At a certain temperature and humidity mosquitoes can not do the lifecycle and inhibite the morfology. The conclusion of this research is the cold storage and extreme temperature influence to eggs hacthingof Strain Japan the Aedes aegypti. Suggestions in this research is the public should continue to implement programs 3M plus, due to the Aedes eggs can survive in cold weather.